2016
DOI: 10.1016/j.eucr.2016.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Extraperitoneal Rupture of a Bladder Diverticulum and the Role of Multidetector Computed Tomography Cystography

Abstract: Nontraumatic rupture of the bladder is less widely recognized than traumatic rupture, with a challenging early diagnosis due to high variability in clinical presentations. We report a case of extraperitoneal rupture of a bladder diverticulum in a patient with diabetes mellitus who presented with paralytic ileus. Despite conservative management, the patient developed sepsis requiring surgical treatment. Urinary tract infection and bladder outlet obstruction were considered to be potential mechanisms of the rupt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 4 publications
0
17
0
Order By: Relevance
“…Pathological bladder‐wall fragility and increased intrabladder pressure are recognized as risk factors for nontraumatic bladder rupture. In our case, sequential CT images suggested that distended bladder caused by acute cystitis provoked bladder rupture on the background of bladder‐wall fragility due to long‐term steroid use 1 and/or diverticulum 2 …”
Section: Introductionmentioning
confidence: 58%
“…Pathological bladder‐wall fragility and increased intrabladder pressure are recognized as risk factors for nontraumatic bladder rupture. In our case, sequential CT images suggested that distended bladder caused by acute cystitis provoked bladder rupture on the background of bladder‐wall fragility due to long‐term steroid use 1 and/or diverticulum 2 …”
Section: Introductionmentioning
confidence: 58%
“…Once exclusion criteria were applied to the abstracts, 352 studies remained for full‐text review. After again applying the exclusion criteria to the full texts, a total of 278 manuscripts remained and were included in the final review […”
Section: Resultsmentioning
confidence: 99%
“…Atraumatic extra-peritoneal rupture of bladder diverticulum is less commonly reported in literature. 18 Pathological bladder wall weakness and/or increased bladder pressures (as a result of bladder outlet obstruction) are harbingers of spontaneous bladder rupture 1 ; predisposing conditions being malignancy, pelvic irradiation, alcohol intoxication, candida cystitis, eosinophilic cystitis, previous bladder surgeries and pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…A bladder diverticulum is mucosal outpouching through the muscular wall of the urinary bladder; cause may be congenital or acquired defect of bladder wall. 1 Congenital bladder diverticula are usually seen as pop-off mechanism in high pressure bladder associated with bladder outlet obstruction such as posterior urethral valves.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation